Anti-erosive properties of solutions containing fluoride and different film-forming agents. Issue 4 (April 2015) - Scaramucci, Taís; Borges, Alessandra B.; Lippert, Frank; Zero, Domenick T.; Aoki, Idalina V.; Hara, Anderson T.
Abstract: Objectives: To evaluate the anti-erosive potential of solutions containing sodium fluoride (NaF, 225 ppm F) and different film-forming agents. Methods: In Phase 1, hydroxyapatite crystals were pre-treated with solutions containing NaF (F), linear sodium polyphosphate (LPP), sodium pyrophosphate tetrabasic (PP), sodium tripolyphosphate (STP), sodium caseinate (SC), bovine serum albumin (BSA), stannous chloride (Sn) and some combinations thereof. Deionized water was the control (C). The pH-stat method was used to evaluate hydroxyapatite dissolution. In Phase 2, the most effective solutions were tested in two independent experiments. Both consisted of an erosion–remineralization cycling model using enamel and dentine specimens with three solution treatments per day. In Phase 2a, the challenge was performed with 0.3% citric acid (pH = 3.8). In Phase 2b, 1% citric acid (pH = 2.4) was used. Hard tissue surface loss was determined profilometrically. Data were analyzed with two-way ANOVA and Tukey tests. Results: In Phase 1, F, LPP, Sn and some of their combinations caused the greatest reduction in hydroxyapatite dissolution. In Phase 2a, C showed the highest enamel loss, followed by LPP. There were no differences between all other groups. In Phase 2b: (F + LPP + Sn) < (F + LPP) = (F + Sn) < (F) = (LPP + Sn) < (LPP) < (Sn) < C. For dentine, in both experiments, only the fluoride-containing groups showed lower surface loss than C, except for LPP + Sn in 2a. Conclusions: F, Sn, LPP reduced enamel erosion, this effect was enhanced by their combination under highly erosive conditions. For dentine, the F-containing groups showed similar protective effect. Clinical significance: The addition of LPP and/or Sn can improve the fluoride solution protection against erosion of enamel but not of dentine.